COMPARISON OF ROUX-EN-Y VERSUS SINGLE LOOP RECONSTRUCTION IN PANCREATICODUODENECTOMY (Journal of Medical & Health Sciences Review, 2025)
Background: Despite advances reducing pancreaticoduodenectomy (PD) mortality to